Characterization of Nucleocytoplasmic Shuttling of Pseudorabies Virus Protein UL46 - Xu, Jing-jing; Gao, Fei; Wu, Ji-qiang; Zheng, Hao; Tong, Wu; Cheng, Xue-fei; Liu, Yuting; Zhu, Haojie; Fu, Xinling; Jiang, Yifeng; Li, Liwei; Kong, Ning; et al. (Frontiers in Veterinary Science, 2020)
Pseudorabies virus (PRV) is the etiological agent of Aujeszky’s disease, which has caused severe economic loss in China since its re-emergence in 2011. UL46, a late gene of herpesvirus, codes for the abundant but non-essential viral phosphoproteins 11 and 12 (VP11/12). In this study, VP11/12 was found to localize both inside the nucleus and in the cytoplasm. The nuclear localization signal (NLS) of VP11/12 was identified as 3RRARGTRRASWKDASR18. Further research identified α5 and α7 to be the receptors for NLS, and the chromosome region maintenance 1 (CRM1) to be the receptor for the nuclear export signal. Moreover, we found that PRV VP11/12 interacts with EP0 and stimulator of interferon genes protein (STING), whereas the NLS of VP11/12 is the imprortant part for VP11/12 to interact with UL48. To our knowledge, this is the first study to provide reliable evidence verifying the nuclear localization of VP11/12 and its role as an additional shuttling tegument protein for PRV. Additionally, this is also the first study to elucidate the interactions between PRV VP11/12 and EP0 as well as between PRV VP11/12 and STING, while identifying the precise interaction sites of PRV VP11/12 and VP16.